A triple-band terahertz metamaterial perfect absorber for biomedical applications and biomarker detection - Mohammad Mahmudul Alam Mia; Md. Ruhul Amin; Sayed Shifat Ahmed; Md. Eyakub Ali; Jannatul Nayem Novera (PLoS ONE, 2026)
This study presents a triple-band perfect metamaterial absorber with a compact microstructured design, achieving near-unity absorption rates of 99.92%, 99.97%, and 99.58% at three distinct terahertz resonance frequencies of 0.925 THz, 1.71 THz, and 2.7675 THz, respectively, for advanced biomedical biosensing applications. The work represents a theoretical and numerical proof-of-concept investigation based on full-wave electromagnetic simulations and refractive-index-assisted biosensing analysis, demonstrating the feasibility of high-sensitivity terahertz detection of biological analytes. The proposed absorber consists of concentric copper ring resonators combined with a central 7-shaped snowflake pattern, developed on an FR-4 dielectric substrate and backed by a continuous copper ground plane. Numerical simulations using the FDTD method were combined with a genetic algorithm approach, enabling the design of high-performance terahertz metamaterials, yielding three sharp, high-Q resonances with near-perfect absorption and ultra-narrow linewidths characteristics. The proposed sensor also demonstrates excellent capabilities including breast cancer cell identification with peak sensitivity of 10,142.86 GHz/RIU, infectious agent recognition, and polarization insensitivity over 0–90°, alongside enhanced absorption tolerance that supports clinical deployment. To evaluate biosensing capability, refractive-index-assisted numerical modeling was performed using literature-reported dielectric properties of biological analytes, including cancer cells, viruses, glucose concentrations, blood components, intracellular materials, and biological tissues. The proposed sensor achieves a maximum sensitivity of 529 GHz/RIU at the third resonance mode with strong linear resonance shifts and high spectral selectivity. Owing to its multi-band terahertz sensor facilitates and strong confinement of electric and magnetic fields at the resonant frequencies enhances the device’s sensitivity to minimal changes in the surrounding medium, allowing for precise, label-free detection of biological analytes including viral variants, malaria pathogens, glucose concentrations, hemoglobin elements, classification of diabetes severity and can also differentiate in anemia categorization across diverse biomedical applications.